ORGANIZATION OF LANGUAGE HIGHER EDUCATION WITH THE USE OF ICT - Tatiana A. Dmitrenko (Высшее образование в России)
Abstract. This article is devoted to the problem of the organization foreign language course in the system of linguistic higher education with the use of information and communication technologies. Peculiarities of forming students’ foreign language competences in a new situation when cross-cultural component is becoming the principal part of foreign language education are considered. The author highlights the role of new technologies in teaching foreign languages, which facilitate an effective communication of specialists of various spheres in a multicultural environment. The article proves the necessity and the objective nature of transformation of the linguistic and educational paradigm – from communicative to intercultural in the conditions of the informatization of our society. The special attention is paid to the professional-focused technology in intercultural communication teaching.